Coaching and Development of Volleyball Based on Social Skills for Positive Youth Development - Dwi Yulia Nur Mulyadi; Amung Mamun; Berliana Berliana; Tite Juliantine (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The holistic approach to developing volleyball skills that incorporates social skills is essential in shaping the character and life skills of young athletes. Social skills such as cooperation, communication, and trust not only impact performance on the field but also shape the morals and values of participants beyond sports. The roles of coaches, teachers, and educators are crucial in guiding students in the world of sports. This study utilized the Quasi Experimental Design "The Matching Only Pretest Posttest Control Group," comparing the treatment group receiving volleyball training integrated with social skills against the control group receiving conventional training. The research aimed to evaluate the impact of integrating sports values on participants' understanding of these values in the context of sports. The research findings indicate that volleyball training integrated with social skills significantly positively impacted the participants' social skill development. Practical recommendations include strengthening cooperation through regular exercises and evaluations, enhancing verbal and nonverbal communication skills, promoting empathy and appreciation for differences, focusing on collaboration within the team, and providing specific training to build trust among team members. Integrating these aspects into sports training programs not only enhances athletes' performance but also equips them with profound social skills. Coaches must take a proactive role as role models, creating youths who are not only skilled in sports but also possess strong social skills. This approach provides a solid foundation for the development of successful athletes and valuable individuals in society.